Ethiopia's 'developmental state' : political order and distributive crisis - Lavers, Tom (African Studies, 2024)
Ethiopia stands out as a leading example of state-led development in Africa. Tom Lavers offers in this book a comprehensive, multi-sector analysis of Ethiopia's development project, examining how regimes maintain power during the extended periods required to bring about economic transformation. Specifically, Lavers explores how the Ethiopian Peoples' Revolutionary Democratic Front (EPRDF, 1991-2019) sought to maintain political order through economic transformation, and why the party collapsed, leading to the outbreak of civil war in 2020. The book argues that the EPRDF sought to secure mass acquiescence through distribution of land and employment. However, rapid population growth and the limits of industrial policy in the contemporary global economy led to a distributive crisis that was a central factor in the regime's collapse. This Ethiopian experience raises important questions about the prospects for economic transformation elsewhere on the continent. This title is also available as Open Access on Cambridge Core at doi.org/9781009428316.